Pengaruh Persepsi Siswa Mengenai Kemampuan Mengajar Mahasiswa PPLK dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X di SMA Negeri 10 Padang - Ayu Lestari Hutajulu; Marwan Usman; Oknaryana Oknaryana (Universitas Negeri Padang, 2018)
This study aims to analyze: 1) the influence of student perceptions about the ability to teach PPLK students on student learning outcomes on economic subjects. 2) the effect of learning motivation on student learning outcomes on economic subjects 3) the influence of student perceptions about the teaching ability of PPLK students an d learning motivation to wards student learning outcomes on economic subjects. The population of this study was all students of class X in 10 N SMA in 2017/2018. A sample of 158 people with a sampling technique in the form of a simple random sampling technique. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results showed that: (1) students' perceptions of the teaching ability of PPLK students had a significant positive effect on student learning outcomes on economic subjects. (2) learning motivation has a significant positive effect on student learning outcomes on economic subjects. (3) the perception of the teaching ability of PPLK students and the motivation to learn together together have a significant effect on the variables of student learning outcomes on economic subjects .Keywords: Learning Outcomes, Student Perception Regarding the Teaching Ability of PPLK Students and Learning Motivation